The Systematical Role of Kant’s Opus postumum. “Exhibition” of Concepts and the Defense of Transcendental Philosophy - Pecere, Paolo (Con-Textos Kantianos. International Journal of Philosophy, 2015)
Kant’s admission of a “gap” in the philosophical system of criticism, which his unpublished project of the “Transition from the Metaphysical Foundations of Natural Science to Physics” would have been meant to fill, has been the object of controversy among scholars. This article reconsiders the problem by connecting the manuscripts with the operation of “exhibition” of concepts, which already had a systematic role in the 1780s, concluding that the new project was intended to provide not a reform, but a necessary complement of previous works. In the final section Kant’s new awareness of this problem in the 1790s is connected to the contemporary reception of criticism (Garve, Reinhold, Maimon, Beck, Schulze, Tiedemann, Fichte). This context provides more evidence supporting the main argument of the article about the inner development of Kant’s thought.
Keywords: Opus postumum; Physics; “Exhibition”; System of Trascendental Idealism